Variação temporal e sazonal na estrutura e reprodução de uma taxocenose de lagartos em uma área de caatinga do alto sertão sergipano - Rocha, Stéphanie Menezes (2012)
In Caatinga environments are frequent catastrophic weather events that ultimately shape the plant and animal life in this biome. Thus, this study aimed to assess how the lizards species of Monumento Natural Grota do Angico, Sergipe, respond to environmental variations in time and seasonal. For this was used information, taken between January 2010 and December 2011, concerning the community structure and reproduction. We recorded 14 species of lizards belonging to eight families. With respect to wealth, there were minor changes between years and between seasons studied. The total abundances and each lizard species varied both between years and between the sites. Tropidurus hispidus prevailed at sites 2 and 3, while Cnemidophorus ocellifer at site 1, in both years studied. The most abundant species at each site in 2010 remained in 2011. Modifications in relation to the dry and rainy seasons in the abundances of lizards did not show. The results of canonical correspondence analysis for years and for the stations showed an association between the occurrence of lizards and environmental variables (number of bromeliads, the proportion of exposed rocks and soil and rainfall). In general, when considering the variety of sites in the years and the stations, the site 1 was the most diverse followed by sites 3 and 2, respectively. Regarding reproduction, it was continuous for C. ocellifer, Lygodactylus klugei and Tropidurus semitaeniatus and probably is linked to the unpredictability of the Caatinga climate. Since T. hispidus reproduce seasonally, coinciding with the rainy season. Cnemidophorus ocellifer and T. hispidus showed differences in activity between the reproductive years, which are related to changes in local precipitation. The size of the litter, C. ocellifer and L. klugei produced up to two eggs at a time, T. hispidus two to four eggs and T. semitaeniatus two eggs per clutch. Cnemidophorus ocellifer, L. klugei and T. hispidus have multiple spawns. Finally, the accumulation of fatty bodies in C. ocellifer did not respond to fluctuations in rainfall and T. hispidus and T. semitaeniatus seem to occur after the period of highest rainfall this environmental variable, but no relation to the reproduction of these animals was observed.